Chapter Rappresentanza e cittadinanza - MASTROPAOLO, Alfio (Studi e saggi, 2023)
One of the characteristics of advanced democratic societies is their fragmentation. This is a serious challenge for the synthesis activity that political representation has the task of carrying out. Right-wing parties, both moderate and populist, can use the concepts of people and nation. The parties of the left no longer use the concept of class and are therefore in serious difficulty. Tony Blair's New Labour has used the concept of citizenship. It was an invention that did not have lasting success, but it certainly helped to make the concept very popular, beyond the boundaries of legal language.